Role of mathematics in chemistry and chemical technology - L. A. Serafimov; A. K. Frolkova; V. S. Timofeev (Тонкие химические технологии, 2010)
A number of aspects determining the role of classical and applied mathematics in natural and applied sciences, particularly, in chemistry and chemical technology is considered. Examples of finding new regularities with the use of mathematical concepts and mathematical tools are given.